Temporal analysis of side effects produced by foam agents in the soil excavated with Earth Pressure Balance (EPB) (2015)
Abstract. The use of foaming agents, is a tunneling technique frequently used with Earth Pressure Balance (EPB) Tunnel Boring Machine (TBM). The main objective of the Materials and Processes for Sustainable Construction (MaPCoD) project is to characterize the treated material with foaming agent, during its evolution over time. Indeed there are few studies presenting a research methodology to evaluate the degradation of pollutant in soils, like the foaming agent used. The foaming agents are surfactant-lubricant chemical compounds. The air system of TBM and foaming agents create bubbles, which are integrated with the soil, this treatment changes the hydro-mechanical properties, allowing easy excavation. Degradation tests (spirometry), viscosity tests (capillary viscometer), mechanical tests (compressibility, consolidation, shear tests and triaxial tests), and curves of water retention over time were used to describe the soil’s behavior. The hydro-mechanical properties are not drastically changed after the treated soil reaches 50% of degradation.